Government's record on health services - Labour Party (Great Britain). Advisory Committee on Public Health
1927-09 1927 1920s 11 pages - 11 - This matter must not be allowed to drop. The health and life and limb of the workers are their only asset and cannot be too strictly safeguarded. The loss of wages due to absence in sickness and accident, or to lowered efficiency whilst at work are sorely felt by the worker and his family. The economic loss to the community from these causes must be far greater than the cost of making proper provision for safeguarding the worker in industry. Only callous indifference and shortsighted and ignorant selfishness on the part of some employers can stand in the way of these reasonable improvements which to-day many of the more enlightened employers are already providing, to their own advantages as well as to the health and comfort of those whom they employ, and the industrial efficiency of the nation. ******* Only two small items can be placed to the credit of the Government in these respects. One is the issue of Regulations, 1927, No. 191, providing for the provision of sanitary conveniences and washing facilities in bake houses. The other has to do with the dry rubbing down process in decorating (already dealt with). 292/840/1/15